PENERAPAN PRINSIP PRINSIP NEW PUBLIC MANAGEMENT DAN GOVERNANCE DALAM REFORMASI ADMINISTRASI - Mohammad Akbar (Universitas Tribhuwana Tunggadewi, 2015)
The successful application of New Public Management (NPM) at some developed countries has cleared path for perpetual promotion of NPM doctrines into developing countries. Privatization is a doctrine in which the service delivered by the government shall be shifted to the hands of private agents. De-bureaucratization is considered as superior because it promises performance improvement if compared to classical public administration. The government of Indonesia starts to acquaint with Reinventing Government since the end of 1990s. The most obvious implementation is the application of decentralist governmental system based on Law No. 22 of 1999 about Local Government which is then amended into Law No. 32 of 2004. New Public Management (NPM) is an important concept and also a significant issue in the public sector reformation. This concept concerns with the problems found in the management of performance at public sector because performance measurement is one of main principles of NPM. The movement of NPM starts from developed countries in European and it has gone far into a global movement such that many developing countries are inspired by the global distribution of this concept. Research attempts to describe New Public Management (NPM), New Public Service (NPS), and Governance in public administration. What will happen with other paradigms after the emergence of New Public Management is also explained. The application of New Public Management and problems behind this application are elucidated. Few illustrations are also given about the difference between Old Public Administration, New Public Management, and New Public Service. The objective of this research is to explain the development and application of New Public Management in public administration / governmental organizations in order to create good governance in decentralization area or wide local autonomy.